FLYPAPER EFFE CT: FENOMENA SERIAL WAKTU DAN LINTAS KABUPATEN/KOTA DI DAERAH AJATAPPARENG PROVINSI SULAWESI SELATAN - Abdillah, Muhammad Abdian (Economos : Jurnal Ekonomi dan Bisnis, 2018)
This study aims to determine the phenomenon of Flypaper Effect in Ajatappareng area of South Sulawesi Province in the last 3 years and to know the condition of regional spending from 2014-2016. This type of research is qualitative research. The object of this research is Local Government of Parepare City, Pinrang Regency and Sidrap Regency. Data collection techniques used documentation to collect budget realization reports for 2014-2016 in the towns of Parepare, Pinrang and Sidrap districts and unstructured interviews to employees of the Parepare Municipal Finance Agency, Pinrang District Financial Agency and the District Financial Administration Agency of Sidrap Regency to collect data additional. The results of this study indicate that (1) there has been Flypaper Effect in the area of ajatappareng South Sulawesi Province in this case Parepare City, Pinrang Regency and Sidrap Regency during 2014-2015 because local government is more likely to use the balance fund than the original revenue area. (2) Expenditure of Kota Parepare, Pinrang and Sidrap Regencies Experienced in 3 years improvement from 2014-2016.